2009
DOI: 10.2471/blt.08.051581
|View full text |Cite
|
Sign up to set email alerts
|

Professional assistance during birth and maternal mortality in two Indonesian districts

Abstract: Objective To examine determinants of maternal mortality and assess the effect of programmes aimed at increasing the number of births attended by health professionals in two districts in West Java, Indonesia. Methods We used informant networks to characterize all maternal deaths, and a capture-recapture method to estimate the total number of maternal deaths. Through a survey of recent births we counted all midwives practising in the two study districts. We used case-control analysis to examine determinants of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 23 publications
5
85
0
Order By: Relevance
“…MMR estimates produced by the capture–recapture method used in this evaluation are likely to be less biased than crude death counts regarding missing events. Finally, the applied asset–based classification of the population into wealth quartiles may not overlap with the governmental method the government uses to stratify population cohorts [13]. …”
Section: Resultsmentioning
confidence: 99%
“…MMR estimates produced by the capture–recapture method used in this evaluation are likely to be less biased than crude death counts regarding missing events. Finally, the applied asset–based classification of the population into wealth quartiles may not overlap with the governmental method the government uses to stratify population cohorts [13]. …”
Section: Resultsmentioning
confidence: 99%
“…At sub-national level, ratios of 212 and 628 have been measured in urban Serang and rural Pandeglang respectively and extremely high levels of 2303 have been demonstrated among the poorest women in these districts (Ronsmans et al, 2009).…”
Section: Study Settingmentioning
confidence: 99%
“…An evaluation study of the safe motherhood programme in Indonesia showed that irrespective of level of socioeconomic status and place of residence (urban vs rural), increasing the number of deliveries by skilled birth attendants (SBAs) did not reduce maternal mortality if most births took place at home 5. In contrast, programmes that enhanced facility-based births in Malaysia and Sri Lanka resulted in marked reduction in maternal and neonatal deaths 6.…”
Section: Introductionmentioning
confidence: 99%